Optimalisasi Tata Letak Gudang untuk Meningkatkan Efisiensi Kegiatan pada PT Radysa Cosmetic - Andreas Panjaitan (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
PT. Radysa Cosmetic is one of the businesses engaged in the distribution of beauty and cosmetic products such as Make Up, Body Care, and Skincare located in Medan City, Jl.Sisingamaraja, Medan Amplas District. However, it has a problem, namely the lack of access points in and out causing disruption to the efficiency of warehouse operational activities so that there is an increase in the number of customers and couriers who come directly to Radysa Cosmetic to make purchases because there is a spike in orders for goods or purchases at the beginning and twin dates every month. The research method used is qualitative in the form of descriptive, where data is collected through direct observation and research as well as interviews with the warehouse head. The results of this study indicate that by implementing the utilization or addition of access points in and out of the warehouse area, it can realize the optimization of the warehouse layout to increase the efficiency of operational activities in the Radysa Cosmetic warehouse.